Development, Dynamics, and Pathology of Neuronal Networks : from Molecules to Functional Circuits : proceedings of the 23rd International Summer School of Brain Research, held at the Royal Netherlands Academy of Arts and Sciences, Amsterdam, the Netherlands, from 25-29 August 2003 - International Summer School of Brain Research 2003 : Amsterdam, Netherlands); Pelt, J. van (Jaap); ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2005)
This book is about neuronal networks within the brain. With roughly 100 billion nerve cells the human brain contains about 3.2 million kilometers of 'wires' to make a million billion of connections between these nerve cells. Nerve cells exchange electrical and chemical signals through these connections and the dynamical patterns of electrical/chemical signals are the basis of all our thinking, memories, consciousness, and control of our behaviour. How do these networks develop their specific connectivity, what are the patterns of electrical activity that serve such a fundamental role in our cognitive abilities, how can it go wrong in these networks resulting in different types of brain pathologies, such as mental retardation, Alzheimer's disease, epilepsy or schizophrenia? These questions are among the most fundamental ones in neuroscience and are addressed in this volume. The chapters in this book cover both state-of-the-art broad reviews and in-depth studies of topics selected in order to bridge different levels of neurobiological organization, from the molecular, cellular, neural network to the cognitive level. An excellent example of such a 'red thread' is given by the chapters devoted to the visual system, illustrating the advanced state of understanding of network development, plasticity and functioning of the visual system. Other chapters illustrate how scientific advances are driven by technical developments as shown for multi-electrode recording and life imaging techniques that enable the study of electrical activity simultaneously in many nerve cells.
Neuronal network formation in human cerebral cortex -- Regulation of dendritic growth by calcium and neurotrophin signaling. Dynamics and pathology of dendritic spines -- Introduction to the sixteenth C.U. Ariens Kappers lecture -- Mechanisms of retinotopic map developments : Ephs, ephrins, and spontaneous correlated retinal activity -- Biologically plausible models of neurite outgrowth. Competition in neurite outgrowth and the development of nerve connections -- Molecular substrates of plasticity in the developing visual cortex -- Excitatory-inhibitory balance and critical period plasticity in the developing visual cortex -- Structural plasticity in the developing visual system. Mechanisms controlling the formation of retinal mosaics -- Laminar circuit formation in the vertebrate retina -- Dynamics and plasticity in developing neuronal networks in vitro -- Learning in ex-vivo developing networks of cortical neurons -- Role of synaptic inhibition in spatiotemporal patterning of cortical activity -- Synaptic mechanisms that shape visual signaling at the inner retina. The involvement of glutamate-gated channels in negative feedback from horizontal cells to cones -- Compensatory physiological responses to chronic blockade of amino acid receptors during early development in spontaneously active organotypic cerebral cortex explants cultured in vitro -- A visual salience map in the primate frontal eye field -- Chronic multiunit recordings in behaving animals : advantages and limitations -- Physiological studies of information processing in the normal and Parkinsonian basal ganglia : pallidal activity in Go/No-Go task and following MPTP treatment -- Rho proteins, mental retardation and the neurobiological basis of intelligence -- Neurodevelopment, neuroplasticity, and new genes for schizophrenia -- The impact of seizures on developing hippocampal networks -- Alzheimer's disease as a disorder of dynamic brain self-organization.
Text in English.
"This event was organized jointly by the Netherlands Institute for Brain Research and the Netherlands Opthalmic Research Institute"--Preface.
Includes bibliographical references and index.
Elsevier
Keywords: Brain -- Research -- Congresses; Neural networks (Neurobiology) -- Congresses; Neurons -- Congresses; Nerve Net -- physiology; Cognition -- physiology; Mental Disorders -- physiopathology; Neurons -- physiology; Synapses -- physiology; Brain -- Research; Neural networks (Neurobiology); Neurons; Neurale netwerken; Electronic books